Safe and cost‐effective protocol for shipment of samples from Foot‐and‐Mouth Disease suspected cases for laboratory diagnostic. Issue 1 (7th April 2017) - Romey, A.; Relmy, A.; Gorna, K.; Laloy, E.; Zientara, S.; Blaise‐Boisseau, S.; Bakkali Kassimi, L.
Summary: An essential step towards the global control and eradication of foot‐and‐mouth disease (FMD) is the identification of circulating virus strains in endemic regions to implement adequate outbreak control measures. However, due to the high biological risk and the requirement for biological samples to be shipped frozen, the cost of shipping samples becomes one of major obstacles hindering submission of suspected samples to reference laboratories for virus identification. In this study, we report the development of a cost‐effective and safe method for shipment of FMD samples. The protocol is based on the inactivation of FMD virus (FMDV) on lateral flow device (LFD, penside test routinely used in the field for rapid immunodetection of FMDV), allowing its subsequent detection and typing by RT‐PCR and recovery of live virus upon RNA transfection into permissive cells. After live FMDV collection onto LFD strip and soaking in 0.2% citric acid solution, the virus is totally inactivated. Viral RNA is still detectable by real‐time RT‐PCR following inactivation, and the virus strain can be characterized by sequencing of the VP1 coding region. In addition, live virus can be rescued by transfecting RNA extract from treated LFD into cells. This protocol should help promoting submission of FMD suspected samples to reference laboratories (by reducing the cost of sample shipping) and thus characterization of FMDV strains circulating in endemic regions.